2020
DOI: 10.1021/acsbiomaterials.0c01189
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Polymer Chemistry and Synthesis Method of PolySTAT, an Injectable Hemostat

Abstract: There is a lack of prehospital hemostatic agents, especially for noncompressible hemorrhage. We previously reported PolySTAT, a unimeric, injectable hemostatic agent, that physically cross-links fibrin to strengthen clots. In this work, we sought to improve the water-solubility and synthesis yield of PolySTAT to increase the likelihood of clinical translation, reduce cost, and facilitate future mass production. First, we focused on side-chain engineering of the carrier polymer backbone to improve water-solubil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
(97 reference statements)
0
16
0
Order By: Relevance
“…Lamm et al, have shown that the quadrivalent PolySTATs increased clot firmness values by 57% and decreased the breakdown values by 69% as compared to phosphate-buffered saline [133]. Furthermore, Lamm et al, also carried out an experiment with PolySTAT to optimize its yield and synthesis method, which could potentially capacitate mass production of PolySTAT and its clinical translation [134]. The primary purpose of the research was to increase the water solubility and yield without compromising the structure and hemostatic efficacy of PolySTAT.…”
Section: Polystatmentioning
confidence: 99%
See 3 more Smart Citations
“…Lamm et al, have shown that the quadrivalent PolySTATs increased clot firmness values by 57% and decreased the breakdown values by 69% as compared to phosphate-buffered saline [133]. Furthermore, Lamm et al, also carried out an experiment with PolySTAT to optimize its yield and synthesis method, which could potentially capacitate mass production of PolySTAT and its clinical translation [134]. The primary purpose of the research was to increase the water solubility and yield without compromising the structure and hemostatic efficacy of PolySTAT.…”
Section: Polystatmentioning
confidence: 99%
“…The primary purpose of the research was to increase the water solubility and yield without compromising the structure and hemostatic efficacy of PolySTAT. From their study, they found that the substitution of hydroxyethyl methacrylate with glycerol monomethacrylate (GmMA) greatly increases the water solubility of PolySTAT without affecting its performance [134]. The hemostatic efficacy of the GmMA-based PolySTAT was verified by an in vivo study of a rat femoral artery bleeding model.…”
Section: Polystatmentioning
confidence: 99%
See 2 more Smart Citations
“…Methacrylate-based random heteropolymers (RHPs) are one such system, which self-assembles into nano-scale particles containing single or few chains in water, and offers an exciting avenue for protein stabilization and mimicry, nanofiltration, and other promising applications. [3][4][5][6][7] . Behavior of methacrylate-based designs in water have been studied most in depth, as many of their applications occur in aqueous environments.…”
Section: Lettermentioning
confidence: 99%